(3OhQ GdfTGW GdHOfj GdQjGVj GdJQHhj aj JYRjR eaGgje GdJQHjI GdUMjI dOi JdGejP GdWhQ GdKGfhj s - (3NGhj, YaGas; (3jhSaj, aJMjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3ef NdGd gPg GdOQGSI fQjO eYQaI OhQ GdfTGW GdHOfj GdQjGVj GdJQHhj aj JYRjR eaGgje GdJQHjI GdUMjI hcPG GdJhUd Edi HfGA HQfGeL aj GdJQHjI GdUMjI hJYRjR eLGdGJgG hOQGSI aYGdjJg CKfGA GdMUI , hJQLY gPg GdOQGSI GdSGHbI ddWGdHI NGhj YaGa aj EWGQ eTQhY GdeGSJQ GdJj GgJeJ HGdLGfH GdWHj, hMjK Cfg CKfGA GdJTNjU JHjf Cfg gfGc Ndd aj GdJQHjI GdUMjI , hYdjg fQjO GdJYejb dcTa SHH GdNdd hGbJQGM Mdg MjK Gff faJQV Ef GdJQHjI GdUMjI hbjGS eOi JWHjbgG JLSjOgG CKfGA GdfTGW GdHOfj GdQjGVj GdJQHhj hcPG EecGfjI (B.(3bjGSgGs
(3OcJhQGIs
Keywords: (3GdJQHjI GdUMjIs; (3GdfTGW GdHOfj GdQjGVj GdeOQSjs